Sustainability in the cocoa-chocolate global value chain: From voluntary initiatives to binding rules? - Jan Grumiller; Hannes Grohs (Austrian Foundation for Development Research (ÖFSE), 2022)
This policy note argues that the low income of cocoa farmers in the cocoa-chocolate global value chain (GVC) is not only a problem in itself, but also exacerbates social and environmental sustainability issues such as child labor and deforestation. The experience of the last two decades has highlighted that private-sector, private-public, and public initiatives were important, but - overall - had insufficient impact on the livelihood of the average cocoa farming household. During the last few years, a shift from voluntary initiatives towards binding rules has emerged in the context of debates on the Living Income Differential (LID) in producer countries and due diligence laws in consumer countries, creating a new window of opportunity. The policy note concludes that - in the current world market situation - higher producer income cannot be ensured without new pricing mechanisms.
Keywords: 330; Kakao; Schokolade; Globale Wertschöpfungskette; Nachhaltigkeit; Welt